Indirect regulation of PCSK9 gene in inflammatory response by Porphyromonas gingivalis infection - Mai Yokoji-Takeuchi; Koichi Tabeta; Naoki Takahashi; Kei Arimatsu; Haruna Miyazawa; Yumi Matsuda-Matsukawa; Keisuke Sato; Miki Yamada; Kazuhisa Yamazaki (Heliyon, 2019)
Pro-protein convertase subtilisin/kexin type 9 (PCSK9), a secreted serine protease, regulates serum low-density lipoprotein (LDL) cholesterol levels by targeting the degradation of LDL receptor (LDLR) in the liver. Although previous reports describe elevated levels of PCSK9 in patients with periodontitis, the mechanisms that trigger this increase in serum PCSK9 levels and induce the related inflammatory response remain unclear. In an unc93b1-deficient mouse of Porphyromonas gingivalis infection, nucleic acid antigen recognition via Toll-like receptors was found to promote PCSK9 production, suggesting an indirect role for tumor necrosis factor-α as an inducer of PCSK9 in contrast to that reported in previous studies. Furthermore, PCSK9 production was independent of the TIR domain-containing adapter-inducing interferon-β-dependent signaling pathway. These results indicate that changes in LDLR expression precede an increase in the serum PCSK9 level in the context of an infectious disease such as periodontitis.